2020
DOI: 10.2139/ssrn.3559128
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Teachers’ Turn Taking Strategies in EFL Classroom Interaction

Abstract: The study of turn taking in EFL classroom interaction is aimed to investigate: (1) the kinds of turn taking strategies that frequently used by male and female teachers in EFL classroom interaction; (2) why the male and female teachers take their turn in EFL classroom interaction; and (3) what are the differences of turn taking used by male and female teachers in EFL classroom interaction. There were four teachers, two male teachers and two female teachers as the subject. They are taken by purposive sampling. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Meanwhile, switching topic of discussion is salient and lecturers need to signal the transition from one topic to another topic or sub-topic by the use of discourse markers so that the students can follow the structure or move of the lecture (Rido, 2010;Walsh, 2011) as this aids comprehension (Kuswoyo et al, 2020;Rido et al, 2017). Next, turn-taking-allocation and student nomination create opportunities for the students to express their ideas and share their voices (Amir & Jakob, 2020;Namaziandost & Nasri, 2019;Sulistyorini, 2019). Rido, Ibrahim, and Nambiar (2015) add that this strategy facilitates less confident or shy students to participate as the lecturer allots them a turn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, switching topic of discussion is salient and lecturers need to signal the transition from one topic to another topic or sub-topic by the use of discourse markers so that the students can follow the structure or move of the lecture (Rido, 2010;Walsh, 2011) as this aids comprehension (Kuswoyo et al, 2020;Rido et al, 2017). Next, turn-taking-allocation and student nomination create opportunities for the students to express their ideas and share their voices (Amir & Jakob, 2020;Namaziandost & Nasri, 2019;Sulistyorini, 2019). Rido, Ibrahim, and Nambiar (2015) add that this strategy facilitates less confident or shy students to participate as the lecturer allots them a turn.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the use of interaction management strategies in secondary and tertiary settings have widely been conducted (Amir & Jakob, 2020;Lovorn & Holaway, 2015;Rido et al, 2017;Rido, Ibrahim, Nambiar, 2015;Rido, 2010;Shi, 2013;Sirande, 2016). The results have shown that interaction management has been significant to promote learning and participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second research was conducted by (Amir & Jakob, 2020). The researchers examine about the kinds of turn-taking strategies, why using turn-takin strategies, and the differences of turn-taking strategies between male and female used in EFL classroom interaction used the theory from (Stenstrom, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They found that each person has a distinct personality that creates a dialogue with a specific pattern. In addition, a study from Amir & Jakob (2020) with the title Male and Female Teachers' Turn Taking Strategies in EFL Classroom Interaction studied the same topic in EFL classrooms focused on the various types of turn taking strategies employed by male and female teachers in EFL classroom communication.…”
Section: Introductionmentioning
confidence: 99%